Editorial (American Journal of Islam and Society, 2007)
In July 2007, the Association of Muslim Social Scientists (AMSS) launchedits new website: www.amss.net. This event signals a reinvigorated AMSSthat seeks to update itself and enhance its professional image. The launchcomes after several years of hard work, conducted mostly behind the scenes,on behalf of the AMSS Executive Board. Under the guidance of Dr. RafikBeekun (president, AMSS), a recognized expert in strategic planning,AMSS has undergone a complete overhaul, from a SWOT (strengths, weaknesses,opportunities, threats) analysis to revising its by-laws and engagingin strategic planning, to implementation.In order to recognize the separate but related nature of Canada to theUnited States (it is not simply the 51st state!), as well as the prominent rolebeing played by Canadian social scientists in AMSS, the board has suggesteda new name: The Association of Muslim Social Scientists of NorthAmerica. This is, of course, contingent upon the membership’s pendingapproval of the new by-laws. In addition, this name change helps identifyus in relation to our sister organizations: AMSS-UK and AMSS-France.Each association is an independent entity sharing a common name, vision,and goals. The first AMSS international conference was held in Istanbul in2006.One theme of AMSS’ new mission statement is that the organizationwill serve as an enabling environment for critical dialogue and debatebetween Muslim and non-Muslim scholars about issues of importance tothe ummah and global society at large. The ability to dialogue is currentlynot one of the Muslim community’s strengths. Dialogue is about talking,about sitting down with people from different backgrounds in order tounderstand their perspective on often controversial issues. The point is notto convince them that your position is the “truth” or vice versa, but to hearthem as fellow human beings and have them hear you. As the NationalCoalition for Dialogue and Deliberation points out, “dialogue is not aboutwinning an argument or coming to an agreement, but about understandingand learning. Dialogue dispels stereotypes, builds trust and enables peopleto be open to perspectives that are very different from their own” (http://-thataway.org/index.php/?page_id=713) ...